2021
DOI: 10.3991/ijet.v16i10.19955
|View full text |Cite
|
Sign up to set email alerts
|

Educational Recommender System based on Learner’s Annotative Activity

Abstract: In recent years, Educational Recommender Systems (ERSs) have attracted great attention as a solution towards addressing the problem of information overload in e-learning environments and providing relevant recommendations to online learners. These systems play a key role in helping learners to find educational resources relevant and pertinent to their profiles and context. So, it is necessary to identify information that helps learner’s profile definition and in identifying requests and interests. In this cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Digital traces (learner behavior) are the key to this type of recommendation. These traces have been used in several works on online learning such as detecting the Learner's motivational state in online learning situation [24], prediction of the Program for International Student Assessment (PISA) score [25] or recommending educational content based on learner's annotative activity [26].…”
Section: Course-based Collaborative Filteringmentioning
confidence: 99%
“…Digital traces (learner behavior) are the key to this type of recommendation. These traces have been used in several works on online learning such as detecting the Learner's motivational state in online learning situation [24], prediction of the Program for International Student Assessment (PISA) score [25] or recommending educational content based on learner's annotative activity [26].…”
Section: Course-based Collaborative Filteringmentioning
confidence: 99%
“…In recent years, educational recommender systems (ERS) have attracted significant attention as a solution for learners. ERS is crucial in helping learners find educational resources relevant to their material and context, and it can also help students to select some adequate courses [15]. Some studies have also shown that recommender systems greatly help and support students' eLearning [3] [25].…”
Section: Machine Learning and Feature Selection 21 Role Of Machine Le...mentioning
confidence: 99%
“…Besides, due to the diversity in the background; various students have various learning demands [2]. Accordingly, it is essential to improve recommender systems to assist learners in choosing courses, resources, or learning materials in E-learning [21]. E-learning has earned popularity due to the COVID-19 pandemic.…”
Section: Advantages Of E-learning During Pandemic Situationmentioning
confidence: 99%